2017
DOI: 10.2196/jmir.6834
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing and Predicting User Participations in Online Health Communities: A Social Support Perspective

Abstract: BackgroundOnline health communities (OHCs) have become a major source of social support for people with health problems. Members of OHCs interact online with similar peers to seek, receive, and provide different types of social support, such as informational support, emotional support, and companionship. As active participations in an OHC are beneficial to both the OHC and its users, it is important to understand factors related to users’ participations and predict user churn for user retention efforts.Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 146 publications
(186 citation statements)
references
References 56 publications
4
164
2
Order By: Relevance
“…Social support refers to an exchange of resources between individuals in order to enhance the well-being of the receiver [10]. Community psychologists have identified different types of social support, which mainly including informational support, emotional support and companionship [9]. Informational support is the transmission of information, suggestion, or guidance to the community users.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Social support refers to an exchange of resources between individuals in order to enhance the well-being of the receiver [10]. Community psychologists have identified different types of social support, which mainly including informational support, emotional support and companionship [9]. Informational support is the transmission of information, suggestion, or guidance to the community users.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, we built classification models to determine what categories of social support each post contains. Consistent with our previous study [9], [20] and aforementioned definitions of social support, we first determined whether a post was seeking informational support (SIS), providing informational support (PIS), seeking emotional support (SES), providing emotional support (PES), or simply inquiring about companionship (COM). The category labels are not mutually exclusive.…”
Section: Page 3314mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Wang et al [18] used text mining techniques to quantitatively analyze online activity related to empowerment. They found that people use online communities mainly to share their personal story and subsequently become less active on the internet.…”
Section: Automated Text Analysis In Empowerment Studiesmentioning
confidence: 99%
“…With respect to the development of user activity over time, Wang et al [18] showed that the participation rate in online communities dropped steeply in a short time span after a user's registration, and that most participation was related to the narrative of the user's own situation. We found similar patterns in the relation between empowerment processes and user activity, suggesting that sharing one's narrative is a means to relate the position of the patient to the new situation they find themselves in, and that the 'giving back to the community' in terms of social or informational support occurs more frequently in the later stages, and among active users.…”
Section: Comparison With Prior Workmentioning
confidence: 99%